2012
DOI: 10.1007/s00248-011-9998-1
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrobacteres: an Important Phylum of Cellulose-Degrading Bacteria

Abstract: The phylum Fibrobacteres currently comprises one formal genus, Fibrobacter, and two cultured species, Fibrobacter succinogenes and Fibrobacter intestinalis, that are recognised as major bacterial degraders of lignocellulosic material in the herbivore gut. Historically, members of the genus Fibrobacter were thought to only occupy mammalian intestinal tracts. However, recent 16S rRNA gene-targeted molecular approaches have demonstrated that novel centres of variation within the genus Fibrobacter are present in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(203 citation statements)
references
References 129 publications
11
189
2
1
Order By: Relevance
“…Most of the OTUs enriched between the rhizoplane and endosphere compartments belonged to Alpha-, Beta-, and Deltaproteobacterial classes, Chloroflexi, and Bacteroidetes. Not surprisingly, a subset of the OTUs enriched in the endosphere and rhizoplane belong to Fibrobacteres and Spirochaetes, phyla that are associated with cellulose degradation (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the OTUs enriched between the rhizoplane and endosphere compartments belonged to Alpha-, Beta-, and Deltaproteobacterial classes, Chloroflexi, and Bacteroidetes. Not surprisingly, a subset of the OTUs enriched in the endosphere and rhizoplane belong to Fibrobacteres and Spirochaetes, phyla that are associated with cellulose degradation (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Commensal or pathogenic strains may have greater access to more labile nutrients than their free-living counterparts, alleviating the necessity for extracellular enzymes. We notably did not detect the ability to use phosphate esters or chitin within Fibrobacteres, a gut symbiont (Ransom-Jones et al, 2012), or Chlamydiae, an obligate intracellular pathogen (Horn, 2008). Recently, Luo et al (2011) found that environmental isolates of E. coli shared a set of genes important for resource acquisition that were absent from enteric isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse cellulolytic species have the capacity to produce celulolase enzymes in aerobic and anaerobic conditions (Kumar et al 2008). It was informed that cellulose global degradation occurs in aerobic conditions in 90% and in anaerobic conditions in 10% (Wei et al 2009;Ransom-Jones et al 2012). The fact that in this work cellulolytic microorganisms were detected in both aerobic and anaerobic environments indicates that the degradation of cellulose occurs in both conditions.…”
Section: Effect Of Stream Channelizationmentioning
confidence: 53%